A migráció gazdaságtana - L. Rédei, Mária (Közép-Európai Közlemények, 2010)
The aim of this paper is to draw the attention of researchers to the gain of spatial mobility. The gain of host countries from the international movement can be strengthening by a better understanding of migration management. The different actors of the movement are able to deliver irregular advocacy of their interest. Although, the national rules are able to keep the security, beyond the legal issues, they have limited efforts. As we know the implementation of flow is happen on a given geographical place. The regional actors had an important role to harmonize the territorial demand and supply, to make a good choice and contribute to integration. The human capital is one of the major out breaking point of the economical crisis. So this is a common interest of the workers and the employers to find the effective solution. The dialogue of host and sending countries is essential, and it should be extended by regional view. By the rising awareness of migrants it is not far the moment, when spatial aspects will corporate the individual interest to do a better daily practice. It looks the student mobility is the most effective way of upgrading the brain, skill and to be familiar by different paths on the world wide.